Oral and maxillofacial radiology during the Coronavirus disease 2019 pandemic : recommendations for a safer practice = Radiología oral y maxillofacial durante la pandemia por Coronavirus 2019 : recomendaciones para una práctica más segura - Cascante Sequeira, Deivi Antonio 1983-
The Coronavirus 2019 disease (COVID-19), was declared a pandemic by the World Health Organization on March 11, 2020, and registered the first case in Costa Rica on March 6, 2020, and 105 days later reported 2058 cases, with a wide age range (0-92 years). Its etiologic agent is the beta coronavirus SARS-CoV-2 with confirmed human-to-human transmission, mainly by the respiratory route. The presence of asymptomatic carriers of the virus and its transmission even without the manifestation of symptoms challenges health professionals worldwide. For this reason, assuming all patients who need dental care as possible carriers of the SARS-CoV-2 is mandatory and consequently, applying biosecurity measures with strict criteria. In the present literature review, we aim to recommend biosecurity measures to be applied during imaging examinations of dental patients due to the Coronavirus-2019 pandemic. We found that in the absence of treatment for COVID-19 disease and because of its high transmissibility, the most effective measures to prevent its spread are those allowing its containment. Therefore, the authors recommend: 1) acquiring imaging exams just in case of dental urgencies or emergencies, 2) prioritizing the use of extraoral exams, such as panoramic radiography or CBCT, under the principle of ALADAI and 3) the intraoral exams should be used just in case of a lack of extraoral imaging devices, or because of the need to solve diagnostic tasks in which they have a superior diagnostic value than those of the extraoral examinations.